Pengaruh Return On Assets Dan Return On Equity Terhadap Capital Adequacy Ratio Di PT. Bank Tabungan Pensiunan Nasional Tbk. Periode 2014-2022 - Ari Sukmawati Diningrat; Anwar Bowo Leksono; Suseno Hendratmoko (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
A bank health assessment is needed to find out whether the condition of the bank is unhealthy, sick or healthy so that the company can take appropriate steps to handle it. The choice of CAR (Capital Adequacy Ratio) as the dependent variable is because according to Bank Indonesia, the Capital Adequacy Ratio is the most important indicator in maintaining the level of bank health. Meanwhile, the choice of ROA (Return On Assets) and ROE (Return On Equity) is because Return On Assets and Return On Equity are aspects of assessing the health of a bank as seen from its ability to generate profits. This research has an important objective to evaluate the financial performance of PT. BTPN Bank by considering ROA, ROE and CAR. With this research, PT. Bank BTPN will know whether the profits generated from Assets and Equity affect the Capital Adequacy value. The sampling technique in this research used purposive sampling, while the sample taken was PT's quarterly financial report. BTPN Bank for the 2014-2022 period consisted of 36 samples obtained through documentation and literature study. From the results of the analysis carried out, the research results show that partially Return On Assets has a positive and significant effect on the Capital Adequacy Ratio, Return On Equity has a negative and significant effect on the Capital Adequacy Ratio, and simultaneously Return On Assets and Return On Equity have a positive and significant effect but not very strong on PT's Capital Adequacy Ratio. National Pension Savings Bank in the 2014-2022 period with evidence of an R Square value of 0.304 or 30.4%.